Penilaian analisa enzim dan isoenzim dalam diagnosa penyakit infarksi miokardia - Sein, Kyam Tun; Raj, S. Mahendra; Ahmad, Zulkifli (1999)
Reference ranges for the following 1 cardiac 1 enzymes and isoenzymes were established, using sera from 99 patients attending the USM outpatients departments: Creatine kinase (CK),lactate dehydrogenase (LD),aspartate aminotransferase (AST),creatine kinase-MB isoenzyme (CKMB) and 5 lactate dehydrogenase isoenzymes (LD1,LD2,LD4 and LD5).The reference ranges for LD1/LD2 ratio, LD1 expressed as percentage of total LD ( LD1%); and LD1 expressed as enzyme activity in International Units LD (IU) were also determined.67 patients who were admitted to the cardiac care unit with suspicion of myocardial infarction were analysed for the above "cardiac" enzymes and isoenzymes. Out of the 67 patients who were admitted to the cardiac care unit ·40 were diagnosed positive and 27 as negative for myocardial infarction. Using the established reference ranges and the diagnoses (positive or negative for myocardial infarction), we determined the sensitivities, specificities and efficiencies for each of the above enzyme/isoenzyme/isoenzyme ratios, at 0-12 hr, 13-24 hr,25-48 hr, and 49-92 hr after the onset of chest pain.For all the above enzymatic parameters the sensitivities were low (42.4 to 68.6) at the interval 0-12 hr, and progressively increased at 13-24 hr (58.7 to 87.1), 25-48 hr (81.1 to 96.9), and 49-92 hr (82.4 to 100) after onset of chest pain. The specificities were higher than sensitivities at 0-12 hr (74.1-100), and 13-24 hr (89.5-96.6). Beyond 25 hr after the onset of chest pain, the specificities were camparable to 13-24 hr except for LD and ID1 ( IU), which had lower specificities compared to earlier pericxis. In general, the best combinations of sensitivities and specificities was during 13-48 hr after onset of chest pain.Based on our data on sensitivities and specificies, it would appear that routine determination of CK-M8 or LD isoenzymes may not be necessary in the diagnosis of most cases of myocardial infarction.